(untitled) (Communications in Computational Physics, 2025)
Consider the inverse problem of time-harmonic acoustic scattering by an unbounded locally rough interface with bounded obstacles embedded in the lower half-space. An extended reverse time migration (RTM) is proposed to simultaneously reconstruct the locally rough interface and embedded obstacles. By constructing a modified Helmholtz-Kirchhoff identity associated with a planar interface and a mixed reciprocity relation, we propose two new imaging functionals with using both the near-field and far-field measurements. It is shown that the imaging functionals always peak on the local perturbation of the interface and the embedded obstacle. Thus, the two imaging functional can be used to reconstruct the location and shape of the rough surface and the embedded obstacle. Numerical examples are presented to demonstrate the effectiveness of the method.